Product attributes and consumer attitudes affecting the preferences for infant milk formula in China – A latent class approach. (January 2019) - El Benni, N.; Stolz, H.; Home, R.; Kendall, H.; Kuznesof, S.; Clark, B.; Dean, M.; Brereton, P.; Frewer, L.J.; Chan, M.-Y.; Zhong, Q.; Stolze, M.
Highlights: Chinese consumers mistrust domestic food supply chains for infant formula. Chinese consumers will pay a premium for authenticity cues and European products. Authenticity cues give assurance: especially when associated with 3rd party controls. Abstract: A series of food safety incidents has led to low levels of trust in the safety of domestically produced Chinese infant milk formula. Concerned parents in China increasingly source 'foreign-produced' brands and use a range of authenticity cues as assurance of the safety and authenticity of infant formula products. However, the effectiveness of authenticity cues in providing assurance to Chinese consumers has not been evaluated. The aim of this study is to analyse the importance of various authenticity cues for infant milk product choices. Latent class models were used to analyse responses to an online choice experiment with 350 consumers of European infant formula in three Chinese cities: Beijing, Guangzhou and Chengdu. The model included respondents' preferences for different labels, authenticity cues and price along with perceptions, attitudes, and socio-demographic characteristics. We identified two consumer segments, with one preferring lower priced infant formula and the second choosing higher priced products. All authenticity cues, including price, appear to serve as indicators of food quality and safety, and all were found to be highly important information sources for the respondents when making purchase decisions. In general, Chinese consumers are prepared to pay a premium for authenticity assurance. Chinese policy makers and the infant formula industry should continue to improve quality control systems to increase consumers' trust in food value chains. These control systems should comprise the whole food supply chain, from production to marketing, and should focus on building trust and communicating credibility.